Functional biscuits enriched with potato peel powder: Physical, chemical, rheological, and antioxidants properties - R. H. Tlay; S. J. Abdul-Abbas; A.А. А. El-Maksoud; A. B. Altemimi; T. G. Abedelmaksoud (Пищевые системы)
This research aimed to replace wheat flour with potato peel powder (PPP) at different levels (3, 5, 7, 10, 30, and 50%). An effect of PPP on physical, chemical, rheological, and antioxidant properties of biscuit samples was investigated. The results show that the PPP sample had a significantly higher content of total sugar, protein and ash, and a lower content of moisture (15.68g/100g dry weight, 15.32 g/100g dry weight, 9.11%, 8.35%, respectively) compared with the wheat flour sample. Also, a higher total phenolic content and antioxidant activity (71.12 mg Gallic acid equivalent / 100g dry weight and 68.39%, respectively) was observed in the PPP sample. The highest percentage of PPP addition (50%) exerted the greatest significant effect on the content of total sugar, protein, moisture, ash, total phenols, and antioxidant activity compared with the control sample and other biscuit samples leading to their increase to 50.90 g/100g dry weight, 12.74 g/100g dry weight, 5.56%, 2.39%, 41.71 mg Gallic acid equivalent / 100g dry weight, 59.72%, respectively. A decrease in the L*, a*, b*, C*, h and BI values, and an increase in ∆E values were observed with replacing wheat flour with PPP. The 3% and 5% replacement rates contributed to improving most organoleptic characteristics (general acceptability, color, taste) compared to the samples with the highest studied percentages (30% and 50%). Although the highest percentages of PPP addition led to lower scores for sensory characteristics, all studied samples were acceptable from the sensory point of view, except the samples with the 50% replacement rate in terms of their taste and color.